Sentiment Analysis Tweet KTT G-20 di Media Sosial Twitter Menggunakan Metode Naïve Bayes - Arta Tirtayasa; Alfian Listiyo Wibowo (Jurnal Pengembangan Sistem Informasi dan Informatika, 2023)
The G-20 or The Group of Twenty is a group consisting of 19 countries with major economies plus 1 European Union. This group was formed in 1999 as a systematic forum with the aim of discussing important issues or problems related to the world economy. The countries included in the G-20 include Australia, Canada, Saudi Arabia, United States, India, Russia, South Africa, Turkey, Argentina, Brazil, Mexico, France, Germany, Italy, United Kingdom, China, India, Japan, and South Korea. From these data it can be concluded that the G-20 Summit is a forum capable of improving the standard of living of many people because of its ability to produce international policies, laws and regulations. Indonesia was once in the world's spotlight because in November 2022, Indonesia will host the G-20 Summit in Nusa Dua, Bali, to be precise. Ordinary people use Twitter to express emotions related to something, both negative and positive emotions. With the implementation of sentiment analysis data from tweets from 500 data tweets using the Naive Bayes algorithm, the result is an accuracy of 69%. The accuracy value with class precision for positive predictions is 78%, while the class precision accuracy value for negative predictions is 36%. The positive class recall accuracy value is 81%, while the negative class recall accuracy value is 32%.